Bat Response to Woodland Restoration within Urban Forest Fragments - Smith, Debra A; Gehrt, Stanley D (Restoration ecology, 2010)
In urban environments, woodland areas are typically fragmented and subject to invasive species encroachment, woody overgrowth, and natural succession. In response to negative impacts, conservationists and land managers have implemented restoration strategies to enhance the integrity of woodlands. Because woodland habitat is important for bats (Order Chiroptera), alterations to forest structures may affect how bats utilize forest fragments in urban environments. We evaluated relationships among restoration efforts, microhabitat characteristics and overall bat activity, and interspecific variation among bats in response to woodland characteristics. We monitored bats in nine woodland forest preserves representing various stages of restoration within the Chicago metropolitan area in 2004 and 2005. Overall bat activity was positively related to prescribed burning, invasive species removal, and small tree density (7.7‐20 cm dbh) and inversely related to shrub density and clutter at 0‐6 m heights. There was interspecific variation in response to alterations in woodland structure, with Lasiurus borealis (L. borealis) positively associated with small and medium (20.1‐33 cm) tree densities and inversely related to clutter at 0‐9 m; Myotis spp. positively associated with canopy cover, clutter at 6‐9 m, and small and medium tree densities; and Lasionycteris noctivagans (L. noctivagans) positively associated with more open forests. Eptesicus fuscus (E. fuscus) activity was not strongly associated with any measured vegetation variable. Our results demonstrate bats positively respond to some forms of woodland restoration in urban landscapes. However, species‐specific responses to vegetation differed and should be taken into consideration when developing management plans.